Passive self-centering hysteretic damping brace based on the elastic buckling mode jump mechanism of a capped column. (1st March 2017) - Wu, Jingzhe; Phillips, Brian M.
Highlights: Elastic buckling mode jump (BMJ) mechanism to generate flag-shaped hysteretic damping. Eccentric capped column design to control onset of buckling and improve damping. Self-centering behavior and reusability. Analytical model of BMJ behavior for design guidance. Seismic lateral system using BMJ performs well and without residual drift. Abstract: Traditional civil structures with yielding systems can be subjected to damage and permanent deformation through major earthquakes, which may induce substantial post-earthquake repair costs and is a critical issue for performance-based seismic design. A novel capped column with an elastic buckling mode jump (BMJ) mechanism is introduced as an economical passive alternative for obtaining flag-shaped hysteretic damping, self-centering and reusability in seismic design. A simple analytical model for the BMJ mechanism is derived and verified with finite element model simulation results for a variety of capped column geometric configurations. Using the validated analytical model, a parametric study is conducted on the geometric properties to provide design guidance. A practical passive self-centering hysteretic damping brace design is also provided in this paper, based on a combination of multiple BMJ mechanisms. The seismic performance of a 3-story frame building under a suite of 20 earthquake ground motions with BMJ brace is compared with a buckling-restrained brace (BRB) frame system as well as a conventional brace (CB) frame system. The results demonstrate the potential of a brace system utilizing BMJ mechanisms to outperform BRB and CB by achieving acceptable inter-story drift response without sustaining residual drift.